Accounting information systems : basic concepts and current issues - Hurt, Robert L. (McGraw-Hill/Irwin, 2010)
Presents AIS as an art as much as a science. This book provides students with vocabulary they will need to succeed in the profession and ensures that they can communicate about accounting information systems with both accountants and nonaccountants